2014
DOI: 10.2478/cpe-2014-0036
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oxygen Staging on Nitrogen Conversion in Oxy-Fuel CFB Environment

Abstract: This paper presents a study on nitrogen conversion in oxy-fuel coal combustion in a pilot scale CFB 0.1 MW th facility. The paper is focused on fuel-N behaviour in the combustion chamber when the combustion process is accomplished under oxy-fuel CFB conditions. The analysis is based on infurnace sampling of flue gas and calculations of the conversion ratios of fuel-nitrogen (fuel-N) to NO, NO 2 , N 2 O, NH 3 and HCN. For the tests, O 2 /CO 2 mixtures with the oxygen content of 21 vol.% (primary gas) and with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
3
6
0
Order By: Relevance
“…Fuel NO x was the main source of NO x under the circulating fluidized bed combustion, and fuel N will be mainly thermal decomposition into NH 3 and HCN and other intermediates . As Figure shows, with the increase of the oxygen concentration in the oxygen-enriched combustion, the NO concentration increases, which is consistent with the former reports. , As a result of the same heat input during the oxy-coal combustion, as the oxygen concentration increased, the flue gas volume decreased . Therefore, NO emissions decreased.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Fuel NO x was the main source of NO x under the circulating fluidized bed combustion, and fuel N will be mainly thermal decomposition into NH 3 and HCN and other intermediates . As Figure shows, with the increase of the oxygen concentration in the oxygen-enriched combustion, the NO concentration increases, which is consistent with the former reports. , As a result of the same heat input during the oxy-coal combustion, as the oxygen concentration increased, the flue gas volume decreased . Therefore, NO emissions decreased.…”
Section: Resultssupporting
confidence: 85%
“…16 As Figure 7 shows, with the increase of the oxygen concentration in the oxygen-enriched combustion, the NO concentration increases, which is consistent with the former reports. 38,39 As a result of the same heat input during the oxycoal combustion, as the oxygen concentration increased, the flue gas volume decreased. 15 Therefore, NO emissions decreased.…”
Section: Co 2 Emissions Undermentioning
confidence: 99%
“…Our experiments showed that switching to oxy-fuel combustion did not alter the NO x emissions. The nitrogen conversion ratio to NO x was up to 24%, similar to results from Jankowska et al [32] with bituminous coal (20-25%). However, Pikkarainen et al [33] measured higher nitrogen conversion ratios (28-50%).…”
Section: Sulfur Oxides Emissionssupporting
confidence: 89%
“…One advantage of oxy-fuel technology is its potentially lower NO x production. Results from different experimental facilities are rather diverse [18,[29][30][31][32][33]. Overall, the results indicate that nitrogen behavior in the oxy-fuel mode is similar to combustion in air and no drastic changes are expected in fuel nitrogen conversion to oxides.…”
Section: Introductionmentioning
confidence: 86%
“…Moreover, the process can decrease emissions of gaseous pollutants, especially if nitrogen oxides (NOx) are taken into account (Jankowska et al, 2014;Toftegaard et al, 2010) Currently, the application of oxy-fuel technology in big-, industrial-scale is still being discussed and considered. The construction of new oxy-fuel boilers is taken into account, although retrofitting an existing power plant to an oxy-firing system (Fei et al, 2015;Fry et al, 2011) provides another solution.…”
Section: Introductionmentioning
confidence: 99%